Pengaruh Proporsi Jenis Belanja, Kebijakan Revisi Anggaran, dan Lokasi Satuan Kerja terhadap Realisasi Penyerapan Anggaran Selama Pandemi Covid-19 pada Satuan Kerja di Lingkup Direktorat Jenderal Kekayaan Negara - Pambudi, Yoga Aditya; Safuan, Safuan; Rizqia, Almira; Alhabsy, Musa Alkadhim; Kasmir, Kasmir; Elmie, Elmie (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the influence of the proportion of types of expenditure, budget revision policy, and work unit location on the level of realization of budget absorption, as well as to determine the joint influence of the proportion of types of expenditure, budget revision policy, and location of work units on the level of realization of absorption. budget during the Covid-19 pandemic in Work Units within the Directorate General of State Assets. This research uses the linear regression method. The data used in this research is secondary data originating from the DJKN Financial Report for Fiscal Year 2020 which has been audited by the BPK with a sample of all work units under DJKN consisting of 1 Head Office, 17 Regional Offices and 72 Service Offices (90 units). The results of this research show that the proportion of types of expenditure and location of work units have a positive effect on the realization of budget absorption, while the budget revision policy has no effect on the level of realization of budget absorption during the Covid pandemic in Work Units within the DJKN scope. In this research, it is also known that the proportion of types of expenditure, budget revision policies, and the location of work units together influence the level of realization of budget absorption during the Covid-19 pandemic in Work Units within the Directorate General of State Assets.